The Effect of Influencer Marketing, Electronic Word of Mouth (E-WOM), and Social Media Marketing On Purchase Decisions for Wardah Glasting Liquid Lip Product: (A Study of Active Female Undergraduate Students at UPN “Veteran” East Java) - Mailis Satus Suhufa Mailis; Maharani Ikaningtyas (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of influencer marketing, electronic word of mouth (E-WOM), and social media marketing on purchasing decisions among female students enrolled in the Bachelor’s Degree Program at UPN “Veteran” East Java. The study employs a quantitative approach, with data collected through a questionnaire distributed to 150 respondents selected using purposive sampling. Data analysis was conducted using IBM SPSS Statistics 26 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that influencer marketing, electronic word of mouth (E-WOM), and social media marketing simultaneously have a positive and significant influence on purchasing decisions. Partially, influencer marketing, electronic word of mouth (E-WOM), and social media marketing also have a positive and significant influence on purchasing decisions among active female undergraduate students in the Bachelor’s Program at UPN “Veteran” East Java. This study demonstrates that digital marketing strategies through influencers, online reviews, and social media can enhance consumers’ purchasing decisions regarding local cosmetic products.